The molecular structure of thio-ether fatty acids influences PPAR-dependent regulation of lipid metabolism. Issue 6 (15th March 2016) - Lund, Jenny; Stensrud, Camilla; Rajender; Bohov, Pavol; Thoresen, G. Hege; Berge, Rolf K.; Wright, Michael; Kamal, Ahmed; Rustan, Arild C.; Miller, Andrew D.; Skorve, Jon
Graphical abstract: Abstract: Thio-ether fatty acids (THEFAs), including the parent 2-(tetradecylthio)acetic acid (TTA), are modified fatty acids (FAs) that have profound effects on lipid metabolism given that they are blocked for β-oxidation, and able to act as peroxisome proliferator-activated receptor (PPAR) agonists. Therefore, TTA in particular has been tested clinically for its therapeutic potential against metabolic syndrome related disorders. Here, we describe the preparation of THEFAs based on the TTA scaffold with either a double or a triple bond. These are tested in cultured human skeletal muscle cells (myotubes), either as free acid or following esterification as phospholipids, lysophospholipids or monoacylglycerols. Metabolic effects are assessed in terms of cellular bioavailabilities in myotubes, by FA substrate uptake and oxidation studies, and gene regulation studies with selected PPAR-regulated genes. We note that the inclusion of a triple bond promotes THEFA-mediated FA oxidation. Furthermore, esterification of THEFAs as lysophospholipids also promotes FA oxidation effects. Given that the apparent clinical benefits of TTA administration were offset by dose limitation and poor bioavailability, we discuss the possibility that a selection of our latest THEFAs and THEFA-containing lipids might be able to fulfill the therapeutic potential of the parent TTA while minimizing required doses for efficacy, side-effects and adverse reactions.